OPTIMALISASI PENGELOLAAN USAHA MELALUI PENINGKATAN PENGELOLAAN MANAJEMEN KEUANGAN KELOMPOK RANTAI EMAS KARTINI II DESA PASAR BANGGI KECAMATAN REMBANG KABUPATEN REMBANG - Agus Widodo; Ming Ming Lukiarti; Novi Kusumaningsih (Buletin Abdi Masyarakat, 2020)
This community service aims to optimize business management through improved financialmanagement in the Kartini Gold Chain Group II in Pasar Banggi village, Rembang Regency. Based oninterviews and analysis of the situation carried out, the problems that can be identified are as follows: 1)Has not been able to manage financial administration optimally, because of limited knowledge andbusiness management that is still simple. 2) Don't have a good financial report 3) Don't have knowledgeabout business management, namely financial management and internal control systems so thatadministrative management is still poor. Based on the problems faced by partners, the solutions offeredare by: 1) Providing knowledge and skills regarding good financial administration governance. 2)Provide knowledge, skills and assistance in preparing good financial reports 3) Provide knowledge, skillsand assistance regarding good business management and internal control. The training is carried outwith the stages of delivery, up to obtaining the target to be achieved, namely 1) Increased knowledge andskills in financial management 2) Increased knowledge and skills in the governance of group financialadministration. 3) Increased knowledge and skills in preparing Financial Statements. Keywords: improvement, management, finance, dedication, pasarbanggi